Hepatocellular Carcinoma in the Adolescent With Classical Familial Adenomatous Polyposis: Clinical Case - Svetlana Ya. Volgina; Ralina R. Ganieva; Zilyara R. Garifullina; Rafik G. Saifutdinov; Eleonora R. Shamsiyeva; Diloram T. Abdullaeva (Вопросы современной педиатрии, 2020)
Background. Hepatocellular carcinoma is rare disease in pediatrics, it affects mostly male adolescents aged 10–15 years. There are only 10 described cases of hepatocellular carcinoma and familial adenomatous polyposis combination.Clinical Case Description. Patient G., 16 years, visited the pediatrician with complaints on low fever episodes and abdominal pain. The abdominal ultrasound was performed. Non-homogeneous mass was revealed in the left lobe of the liver. Contrast X-ray computer tomography has revealed large pathological mass in the left lobe of the liver (atypical haemangioma? adenoma?). Adenoma phenotype was established in obtained needle biopsy material. The child has undergone the resection of the left lobe of the liver with plastic reconstruction of the left hepatic vein entry. Histological examination of the surgical specimen has confirmed the presence of hepatocellular carcinoma. Peripheral blood α-fetoprotein levels remained within normal range throughout the follow-up. In past medical history: classical familial adenomatous polyposis in the mother (diagnosis has been established 3 years before the clinical events in the child). The genetic testing of APC gene (Adenomatous Poliposis Coli) was performed after detection of the tumor in the child’s liver. The pathological allele similar to that previously found in the mother has been identified. Conclusion. Timely diagnosis of familial adenomatous polyposis, risk awareness on combined course of polyposis with various malignant tumors, as well as monitoring of health condition of the child are necessary to diagnose hepatocellular carcinoma on its early stages.